2021
DOI: 10.1007/s10562-020-03494-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved Activity and Stability of Chlorobenzene Oxidation Over Transition Metal-Substituted Spinel-Type Catalysts Supported on Cordierite

Abstract: Industrial catalysts usually encounter great challenges in Cl• deactivation, toxic by-products generation, and stability with a long running operation for catalytic oxidation of chlorinated volatile organic compounds (CVOCs). In this research, spinel-type oxides with transition metal substituted as active oxides supported on cordierite (Crd) was identified to catalytic degradation of chlorobenzene (CB). The Cu1.4Mn1.6O4 spinel-type oxides considered as the main active oxides have been identified, which were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Effects of morphology. Manganese oxides with different morphologies such as rod, 85 tubes, 89 lamellar, 89 porous, 53 hollow, 47 spinels, 87 and perovskite 97 structures for CBCs oxidation were investigated. γ-MnO 2 (rod-shaped) exhibited higher activity and stability than α-MnO 2 (tubular) and δ-MnO 2 (lamellar), which were due to abundant surface oxygen vacancies.…”
Section: Influence On Manganese-based Catalystsmentioning
confidence: 99%
See 3 more Smart Citations
“…Effects of morphology. Manganese oxides with different morphologies such as rod, 85 tubes, 89 lamellar, 89 porous, 53 hollow, 47 spinels, 87 and perovskite 97 structures for CBCs oxidation were investigated. γ-MnO 2 (rod-shaped) exhibited higher activity and stability than α-MnO 2 (tubular) and δ-MnO 2 (lamellar), which were due to abundant surface oxygen vacancies.…”
Section: Influence On Manganese-based Catalystsmentioning
confidence: 99%
“…It also proved that the introduction of CeO 2 promoted the ring opening in the presence of adsorbed oxygen and hydroxyl radicals to remove Cl • on benzene. 87 Controlling the morphology to get a more exposed surface of active sites. Adjusting the microstructure is an effective way to improve the activity of catalysts.…”
Section: Activity Enhancement On Manganese-based Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development and synthesis of monolithic catalysts with excellent oxidation activity and stability are of great signi cance in industrial application. We have studied on the effect of CuA x Mn 2−x O 4 /Cordierite (A = Cr, Fe, Ce; x = 0.25, 0.5, 1) catalysts for catalytic oxidation of CB (Huang et al 2021), previously. It had been demonstrated that CuCe 0.25 Mn 1.75 O 4 /Cordierite catalyst exhibited the high activity and good stability owing to that CeO 2 nano-rods structure conducive to increase the amount of O ads and the strength of weak acidity.…”
Section: Introductionmentioning
confidence: 99%